Comparison between viscous lignocaine and rectal diclofenac for immediate postoperative analgesia in paediatric tonsillectomy - Zayuah, Mat Sulaiman (Universiti Sains Malaysia, 2008)
Tonsillectomy is a common surgical procedure in children. Pain after tonsillectomy is inevitable and causes not only distress, but also dehydration, difficulty in eating and delayed post-operative recovery. Previous studies in the pediatric population have demonstrated a significant decrease in post operative pain and morbidity by using local analgesic but the effectiveness in relieving pain has not been formally assessed and there is no study done using viscous lignocaine for the pain reduction following tonsillectomy. It is very important to determine weather topical can replace other form of medication in the management of immediate post-operative pain. Objectives The goal of this study was to find out the effectiveness of viscous lignocaine for immediate pediatric post-tonsillectomy pain in comparison to r~ctal diclofenac. ' Specific objective include to determine weather peri-operative viscous lignocaine effectively reduces immediate incisional pain in tonsillectomy patients using Visual Analogue Score (VAS) between the groups and reduction in post-operative analgesic requirement as a rescue analgesic in pediatric tonsillectomy patients. It also to assess the ability of the patients following tonsillectomy to start oral feeding. Vl Methodology 130 patients aged between 5 to 12 years old were randomly allocated to two groups to receive either viscous lignocaine or rectal diclofenac as post-operative analgesic. Patients will be randomized into 2 groups, using computer generated simple random sampling. 65 patients are assigned into group A ( viscous lignocaine ) and another 65 in group B ( rectal diclofenac ). Group A : Patients given 3 mls of viscous lignocaine 2 % or maximum of 4mg/kg body weight whereas Group B : Patients were given rectal diclofenac 1 mg/kg. All patients will be preoxygenated with oxygen and induced with intravenous fentanyl 1.5mcg/kg, propofol 2 mg!kg and rocuronium 0.5 mg!kg as muscle relaxant. In the recovery room, vital signs will be charted and pain assessment was done using VAS 0.5-hour and before discharge to ward. In the ward, patients is then follow up for 24 hours by Acute Pain Service team and time of resumption oral feeding and total rescue medication is recorded at 1-hour, 2-hour, 4-hour, 12-hour and 24-hour. If patients complaining of intolerable pain, rescue medication will be given, intravenous pethidine 0.5 mg/kg and time, frequency and total doses will be recorded at the same time interval. Result 130 patients completed the study. The result showed that even though statistically not significant, p=0.4 79; the VAS score was lower in viscous lignocaine group first 4 hours post-operatively. Haemodynamically, the MAP was significantly reduce in viscous lignocaine group after 4-hour with p=0.043, at 12-hour p=0.040 and at 24-hour p=0.044. The dose of rescue medication was significantly reduced at 2-hour postoperation with p=0.023 and the dose still reduced at 4-hour post-tonsillectomy. The time for resumption oral feeding were also significantly reduced for oral fluid and oral soft Vll diet in viscous lignocaine group with p=0-016 and p=0.007 respectively. Conclusion From our study, we conclude that viscous lignocaine is comparable to rectal diclofenac for post-tonsillectomy analgesia in paediatric patients. Viscous lignocaine does reduced significantly immediate post-operative pain and result in early return of oral feeding. It is safe and can reduce the unnecessary complication of systemic analgesia.